el docente universitario ante los bienes de su práctica - (:unkn) unknown (Universidad Industrial de Santander, 2015)
We can recognize the teacher and his profession as the attempt to research or to discover, recognize, promote and teach the truth to others. The scope of a teacher’s quality is a topic still debated by those who tackle the issue in its objective and modern significance on the one hand, and those who consider it in its vocational meaning, on the other hand. This article puts forward the notion that it is possible to synthesize these two ways of tackling the meaning of a profession. It also puts forward the idea that efficacy of teaching is defined first by its own objectives—it is not the professional that creates those objectives— and by the availability of the professional. Therefore, a professional teacher is that who can teach his pupils in the best way so that they grasp the objectives and particularities of university education
Published in Journal of Universidad Industrial de Santander, Colombia
We can recognize the teacher and his profession as the attempt to research or to discover, recognize, promote and teach the truth to others. The scope of a teacher’s quality is a topic still debated by those who tackle the issue in its objective and modern significance on the one hand, and those who consider it in its vocational meaning, on the other hand. This article puts forward the notion that it is possible to synthesize these two ways of tackling the meaning of a profession. It also puts forward the idea that efficacy of teaching is defined first by its own objectives—it is not the professional that creates those objectives— and by the availability of the professional. Therefore, a professional teacher is that who can teach his pupils in the best way so that they grasp the objectives and particularities of university education
Keywords: discover; recognize; promote; teach; synthesis; professionalism; practice; professional teacher; pupils; university education.